Perilaku Main Seller dalam Penetapan Harga Barang Thrifting Fashion di Surabaya - Ramdhan, Qory Azis Alamsyah; Prabowo, Prayudi Setiawan (Jurnal Ekonomika : INDEPENDEN, 2023)
The phenomenon of buying and selling used goods or Thrifting has been widely practiced by the people of Surabaya. This activity has been carried out a lot both on the side of the road or in terms of stalls, as well as through offline stores, as well as online shops. With the rise of these used clothing sellers, Surabaya has become one of the cities selling centers for Thrifters. This study aims to examine and analyze the influence of the Main Seller's behavior in setting the price of low-cost goods in the city of Surabaya. This study uses a qualitative research method with a phenomenological approach. The results of this study indicate that the quality factor of Thrifting goods is a fundamental factor for the Main Seller in setting the price of an item.